Education for Social Justice through Sustainable Development, Economic Development and Equity - Zayd Waghid, Zayd Waghid (South African Journal of Higher Education, 2018)
In this article I argue that (higher) education for social justice is an encounter, as it invokes both the capacities and cultural stock of individuals and groups. Considering that social justice is inextricably connected to need, desert and equality, it seems plausible to claim that (higher) education for social justice ought to be responsive to the aforementioned demands. I show how (higher) education for social justice seems to manifest in instances such as sustainable development, economic development and equity (not at the expense of equality, but rather as a shift in focus from striving towards equity in an equal manner). And, drawing on the seminal works of Bell, Hooks and Hackman, cultivating equal participation (through deliberation, self-reflexivity and openness), contesting dominance and privilege, and developing a critical understanding and awareness to enact social change respectively seem to be the ingredients for engendering an education for social justice in and beyond the university classroom. Keywords: Education, Social Justice, Teaching, Learning, Need, Desert, Equality, Sustainable Development, Equity and Economic Development